English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

If you can explain little bit, that would be even better
thank you

2007-02-06 15:07:33 · 4 answers · asked by Anonymous in Science & Mathematics Mathematics

4 answers

Alright, here's the derivatives you need to know:
d/dx(log_b (x)) = 1/(ln(b)x) (b is the base of the log)
d/dx(ax) = a
and you need to know the chain rule: d(f(g(x)))/dx = f'(g(x))*g'(x)

So by chain rule:
d/dx(log_3 (1+ xln3))=
1/(ln(3)*(1+xln3)) * d/dx(1+x*ln3)=
1/(ln(3)*(1+xln3)) * (0 + ln3)=
ln(3)/(ln(3)*(1+xln(3)))=
1/(1+xln(3)

2007-02-06 15:29:00 · answer #1 · answered by Ben 6 · 0 0

The derivitive of one is zero. With xln(3), you must use the product rule here. The first times the derivative of the second, plus the second times the derivative of the first.

y`=x*0+1*ln(3)

y`=0+ln(3)

y`=ln(3)

2007-02-06 23:24:29 · answer #2 · answered by seymour 2 · 0 1

First, remember that the derivative of ln(x) = 1/x, and that log base 3 (z) = ln(z)/ln(3)

Chain rule all the way:

d/dx (log base 3 (1 + xln(3)))

= d/dx (ln(1+xln(3))/ln(3))

(1/(ln(3) * (1+xln(3)))) * ln(3) = 1/(1+xln(3))

2007-02-06 23:19:47 · answer #3 · answered by mrfahrenbacher 3 · 1 0

You may try another brand

let y = Log(at 3) {1 + x Log(at e) (3) }

take both sides to the base " 3" like we take exponential

(3)^y = {1 + x Log(at e) (3) } ... (1)

differentiate wrt x
(3)^y Log (at e) (3) . dy/dx = 0 + 1* Log(at e) (3)

(3)^y . dy/dx = 1

dy/dx = 1/ (3)^y = 1 / {1 + x Log(at e) (3) } from (1)

Answer - do it differently

2007-02-07 09:41:17 · answer #4 · answered by anil bakshi 7 · 0 0

fedest.com, questions and answers